Como os influenciadores utilizam o marketing digital para influenciar seus seguidores - Silva, Gabriel da Silva e (Brasil, 2025)
This paper presents the topic of the use of digital marketing, with an emphasis on its application by digital influencers. The article aims to address the influence of influencers on people, whether in purchasing decisions or lifestyle habits. Its main objective is to clarify the tools used by influencers through digital marketing to influence people. The methodology adopted was a bibliographic review, collecting information from articles and scientific journals in databases such as Scielo, as well as websites on the internet related to the topic. Field research was also conducted, with the application of an online questionnaire to university students from the Federal University of Amazonas. The research results were considered positive, as the objective was successfully achieved.